Subclasses of uniformly starlike functions - Ed Merkes; Mohammad Salmassi (International Journal of Mathematics and Mathematical Sciences)
We study subclasses of the class of uniformly starlike functions which were recently introduced by A.W. Goodman. One new subclass is defined and it is shown that it shares many properties of the parent class.